Improving heating plant emissions using flue gas carbon monoxide monitoring : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Engineering in Automation and Control at Massey University - Al Shukairi, Jokha Hamood (Massey University, 2011)
RCR Energy Systems builds industrial heating plants and their control systems. In these the excess air (above the stoichiometric ratio) for combustion is a process variable and its setpoint is determined using a look-up table. RCR aims to improve the efficiency of wood-fired, thermal-oil heating plants by using a combination of carbon monoxide monitoring and oxygen trim control to automatically adjust the excess air setpoint. Heating plants require the correct amount of oxygen for combustion. Too little excess air does not allow complete combustion, producing a loss in efficiency and wasted fuel. Too much excess air reduces the flame temperature with a consequent drop in heat transfer rate and loss of efficiency. The aim of the project was to explore the advantages of carbon monoxide monitoring and oxygen trim control, as well as its application, design and implementation in trimming excess oxygen setpoint, to a lower, but still safe operating level. Various carbon monoxide monitoring and oxygen trim control schemes were researched with the most suitable being implemented on an industrial system using a combined carbon monoxide and oxygen measurement analysers. This scheme was then tested on the heating plants at Hyne & Son in Tumbarumba, Australia. The tests proved that the excess air setpoint could be successfully reduced by 2%, leading to an approximate 3 – 5% improvement in efficiency.
Keywords: Heating plants; Environmental aspects; Carbon monoxide detectors; Measurement; Air quality management